Struktur Retorika Karangan Narasi Mahasiswa Pendidikan Guru Sekolah Dasar STKIP PGRI Lubuklinggau - Sri Murti (ESTETIK : Jurnal Bahasa Indonesia, 2018)
The research aims was to describe the structure of a Narrative Essay rhetoric Describing Student primary school teacher education STKIP PGRI Lubuklinggau, using qualitative research methods. As for the steps in analyzing the following: a). data analysis will be started from an analysis of the "text" of the text of a collection of short stories which is read repeatedly, b). After that number sort on a collection of short stories, followed by c). give the numbers sort as well on each of the paragraphs in the short story collection, d). Then give the code based on the categories of items that appear in each paragraph (identify text elements), e). Make a general description of the sheet structure of rhetoric that appeared every paragraph, f). Further describes and discusses the results of data analysis, g). Draw conclusions from the results of research. The results of this study show that in general the rhetoric of narrative essay with using theory of generic text labov has a pattern variable that is 1). O contained on the (KR 8 dan KR 18), 2). O – PP contained on the (KR 3, KR 4,KR 5,KR 7, KR 13, KR 17,KR 20, KR 22,KR 24, KR 27, R 28, KR 29, KR, 32,dan KR 34), 3). O – PP – R contained on the ( KR 1, KR 2,KR 6,KR 9,KR 10, KR 11,KR 12,KR 14, KR 16,KR 19, KR 21,KR 23, KR 25 dan KR 26,dan 4). O – PP – R – K contained on the (KR 15,KR 30 dan KR 31). Beside it from 33 describing These consist of 33 bouquet that has elements of orientation (O), the describing has elements of perumitan events (PP) totaled 29 describing while elements of the resolution (R) totaled 17 describing, and last element of koda (K) amounted to 3 wreaths. Here's an explanation of each of the structures contained in the narrative essay. Keyword: Rethoric Structure, Describing, and Narrative